Influence of Age and Other Factors on Cytokine Expression Profiles in Healthy Children—A Systematic Review - Decker, Marie-Luise; Grobusch, Martin P.; Ritz, Nicole (Frontiers in Pediatrics, 2017)
Cytokines have attracted much attention as diagnostic biomarkers for infectious and inflammatory diseases in recent years. However, understanding of maturation and normal age-associated values is limited. This review summarizes evidence on the influence of age and other factors on expression profiles of soluble and intracellular cytokines in healthy children. IFN-γ, IL-6, IL-10 and TNF-α are the most frequently investigated cytokines, of which an age-associated increase was shown consistently for IFN-γ and TNF-α. An age-associated decrease of IL-13 was seen in resource-limited settings. For other cytokines including IL-1RA, IL-2 and IL-10 uni- or bimodal curves have been described, and results were influenced by study setting. To conclude, despite limited current understanding of the development of cytokine expression age clearly influences expression profiles in healthy children. Dynamics of cytokine expression in childhood need to be considered when these are measured in diagnostic assays or as biomarkers. In addition, cytokine-targeting agents may require adjustment for normal values when used in children.